Angiotensinergic receptors in the medial amygdaloid nucleus differently modulate behavioral responses in the elevated plus-maze and forced swimming test in rats - Moreno-Santos, Beatriz [UNESP]; Marchi-Coelho, Camila [UNESP]; Costa-Ferreira, Willian [UNESP]; Crestani, Carlos C. [UNESP] (Elsevier, 2021)
The brain renin-angiotensin system (RAS) has been implicated in anxiety and depression disorders, but the specific brain sites involved are poorly understood. The medial amygdaloid nucleus (MeA) is involved in expression of behavioral responses. However, despite evidence of the presence of all angiotensinergic receptors in this amygdaloid nucleus, regulation of anxiety- and depressive-like behaviors by angiotensinergic neurotransmissions within the MeA has never been reported. Thus, the present study aimed to investigate the role angiotensin II (AT1 and AT2 receptors) and angiotensin-(1–7) (Mas receptor) receptors present within the MeA in behavioral responses in the elevated plus-maze (EPM) and forced swimming test (FST). For this, male Wistar rats had cannula-guide bilaterally implanted into the MeA, and independent sets of animals received bilateral microinjections of either the selective AT1 receptor antagonist losartan, the selective AT2 receptor antagonist PD123319, the selective Mas receptor antagonist A-779 or vehicle into the MeA before the EPM and FST. Treatment of the MeA with either PD123319 or A-779 decreased the EPM open arms exploration, while losartan did not affect behavioral responses in this apparatus. However, intra-MeA microinjection of losartan decreased immobility in the FST. Administration of either PD123319 or A-779 into the MeA did not affect the immobility during the FST, but changed the pattern of the active behaviors swimming and climbing. Altogether, these results indicate the presence of different angiotensinergic mechanisms within the MeA controlling behavioral responses in the FST and EPM.
Keywords: Amygdala; Angiotensin; Anxiety; Depression; Rodents; Stress